PENGARUH ASIMETRI INFORMASI, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP MANAJEMEN LABA (Studi Pada Perusahaan Manufaktur Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2009-2013) - Randi Tri Rahmando (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
This study, entitled The Effect of Information Asymmetry, company size and leverage to earnings management. The purpose of this study was to determine the effect of information asymmetry, firm size and leverage simultaneously, partial and calculate how big influence on earnings management. This research is using secondary data. The population in this study manfaktur food and beverage companies listed on the Stock Exchange in 2009-2013. The sample in this study amounted to 13 companies. Data analysis techniques using multiple linear regression analysis with panel data. These results indicate asymmetry and leverage information can not significantly affect earnings management, company size significantly affect earnings management.Keywords: Effect of Information Asymmetry, Company Size and Leverage to Earnings Management.